Analisa Persediaan Obat dengan Menggunakan Analisa ABC dan Kelas Terapi di Poliklinik RSK St. Vincentius A Paulo - , Fransisca Mulyani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to determine the inventory of drugs that have an investment value of high, medium and low. The result of this research will be used as a suggestion or recommendation for improvements in the procurement and cycle count. The object of this study was The Outpatient Unit in St. Vincentius a Paulo Catholic Hospital Surabaya. Using the data of items, usage and unit costs of medicine from Januari 2011 through December 2011. Supply of drugs was analyzed using ABC Analysis and Therapeutic Category Analysis. From the result of these analysis showed the kind of medicine and Therapeutic Category that has investment value of high, medium and low which is to determine the level of medicine procurement and cycle count. ABC Analysis results are as follows: Class A as many as 208 items or 19,6 % with an investment of 75,00%. Class B as many as 175 items of medicine or 16,49 % with an investment of 15,05 % and Class C of 678 items or 63,90 % with an investment of 9,95 %. The results of the Therapeutic Category Analysis showed that there are 6 theurapetic category of drugs included in the Class A.: Antimicrobial , Cardiovascular, Hormonal, Nutrition, Respiratory and Gastrointestinal drugs. Class A consists of 778 items of medicine which is 79,60 % drug invenoty investment. There are 2 therapeutic category of drugs included in the Class B: Antiinflamatory - Analgesic drugs and Nerve system drugs which consists of 178 items or 16,78 % and 13,39 % is the investment value of drugs. There are 4 Therapeuttic Category are included in Class C, namely: Renal & Electrolyte, Hematologic drugs, Anti Neoplastics, Chemoprotectants, Immunosuppressant and Vaccine. There are 95 item of drug or 8,95 % or 7,01 % the investment value of drugs.